Exploring the Regulatory Function of the N‐terminal Domain of SARS‐CoV‐2 Spike Protein through Molecular Dynamics Simulation. Issue 10 (2nd September 2021) - Li, Yao; Wang, Tong; Zhang, Juanrong; Shao, Bin; Gong, Haipeng; Wang, Yusong; He, Xinheng; Liu, Siyuan; Liu, Tie‐Yan
Abstract: SARS‐CoV‐2 is what has caused the COVID‐19 pandemic. Early viral infection is mediated by the SARS‐CoV‐2 homo‐trimeric Spike (S) protein with its receptor binding domains (RBDs) in the receptor‐accessible state. Molecular dynamics simulation on the S protein with a focus on the function of its N ‐terminal domains (NTDs) is performed. The study reveals that the NTD acts as a "wedge" and plays a crucial regulatory role in the conformational changes of the S protein. The complete RBD structural transition is allowed only when the neighboring NTD that typically prohibits the RBD's movements as a wedge detaches and swings away. Based on this NTD "wedge" model, it is proposed that the NTD–RBD interface should be a potential drug target. Abstract : The Spike protein of SARS‐CoV‐2 plays a key role in the infection process. The N ‐terminal domain (NTD) of the Spike protein plays a regulatory function by the "wedge" model: it typically wedges in to prohibit receptor binding domain's (RBD's) movements and occasionally moves out to allow RBD to tilt downward. Potential drugs are virtually screened for the NTD‐RBD interface.